2023
DOI: 10.1111/gcb.17006
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic disturbance exacerbates resilience loss in the Amazon rainforests

Huan Wang,
Philippe Ciais,
Stephen Sitch
et al.

Abstract: Uncovering the mechanisms that lead to Amazon forest resilience variations is crucial to predict the impact of future climatic and anthropogenic disturbances. Here, we apply a previously used empirical resilience metrics, lag‐1 month temporal autocorrelation (TAC), to vegetation optical depth data in C‐band (a good proxy of the whole canopy water content) in order to explore how forest resilience variations are impacted by human disturbances and environmental drivers in the Brazilian Amazon. We found that huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Thus, to avoid misinterpreting HLU changes after 2020 (DeArmond et al, 2023;INPE, 2023) as resilience changes, we only analyze pre-2020 years. In particular, Wang et al (2024) recently showed that anthropogenic influence highly affects resilience in the ARF. Thus, to be as rigorous and conservative as possible, we also exclude any cell with more than one percent forest loss during 2001-2020, using the values from Hansen et al (2013).…”
Section: Grid Cell Selectionmentioning
confidence: 99%
“…Thus, to avoid misinterpreting HLU changes after 2020 (DeArmond et al, 2023;INPE, 2023) as resilience changes, we only analyze pre-2020 years. In particular, Wang et al (2024) recently showed that anthropogenic influence highly affects resilience in the ARF. Thus, to be as rigorous and conservative as possible, we also exclude any cell with more than one percent forest loss during 2001-2020, using the values from Hansen et al (2013).…”
Section: Grid Cell Selectionmentioning
confidence: 99%
“…As landscapes are increasingly altered by human activities, a predictive understanding of how areas with high vegetation resilience are impacted by human activities can inform conservation efforts, such as protected area (PA) planning and management, especially in the face of increasing climate extremes (Wang et al, 2024;Wilson et al, 2020). One of the most widespread human impacts on ecosystems is land conversion, which can affect vegetation climate resilience by intentionally or unintentionally converting areas with high vegetation resilience, by influencing natural landscape features, or by reducing habitat heterogeneity (Nimmo et al, 2015).…”
mentioning
confidence: 99%